Immunogenicity study of infectious bursal disease virus vaccines in commercial broiler chickens - Dastjerdi, P. Zarghami; Bejo, M. Hair; Abd Rahaman, N. Y.; Omar, A. R. (Malaysian Veterinary Medical Association, 2024)
The infectious bursal disease (IBD) is a highly contagious viral disease affecting young chickens, causing bursal depletion and leading to economic losses where biosecurity and vaccination are considered the most effective control measures. This study compared the immunogenicity of the commercially available herpesvirus of turkey (HVT) vector vaccine (HVT+IBD) and a live attenuated plus IBD vaccine (IBD+) in commercial broiler chickens. Vaccines were administered to broilers per manufacturer’s guidelines, where the HVT+IBD vaccine for day-old chicks subcutaneously and the IBD+ vaccine for day 12 via eye/oral drop. Serological responses were evaluated using IDEXX and IDvet ELISA kits. The broiler chickens had high maternally derived antibody (MDA) titers detected by both ELISA kits prior to vaccination. At day 28, both HVT+IBD and IBD+ vaccines elicited strong antibody responses, 5992.33 ± 3817.29 and 4775.00 ± 3418.77, respectively. High seroconversion antibody was detected from the IBD+ but not from the HVT+IBD vaccinated birds. Bursal histopathological analysis showed mild bursal lesion in the HVT+IBD vaccinated group 0.54 ± 0.44, whereas the IBD+ vaccinated group exhibited moderate bursal lesions (3.00 ± 0.22). Additionally, seroconversion of the HVT+IBD vaccinated chickens is associated with replication of the HVT vaccine in the bursa and spleen as detected by qPCR. This study showed while both vaccines can elicit high antibody titers, a successful vaccination of the HVT+IBD vaccine associated with high seroconversion and minimal bursal lesions, highlighting the importance of vaccine choice against IBD.